Abnormal Liver Tests during Hospitalization Predict Mortality in Patients with COVID-19: A Multicenter Study from South America - Domingo Balderramo; Angelo Z. Mattos; Victoria Mulqui; Talita Chiesa; Zuly Plácido-Damián; Jaysoom Abarca; Andrea Bolomo; Yanina Carlino; Isadora Z. Bombassaro; Denusa Wiltgen; Laura Tenorio Castillo; Karina Díaz; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. The role of liver function tests (LFT) as prognostic factors in patients admitted with COVID-19 has not been fully investigated, particularly outside resource-rich countries. We aimed at evaluating the prognostic value of abnormal LFT on admission and during hospitalization of patients with COVID-19. Methods. We performed a retrospective study that included 298 adult patients hospitalized for COVID-19, between 05/2020 and 02/2021, in 6 hospitals from 5 countries in South America. We analyzed demographic and comorbid variables and laboratory tests on admission and during hospitalization. LFT over twice the upper limit of normal (ALEx2) were also evaluated in relation to a variety of factors on admission and during hospitalization. De novo-ALEx2 was defined as the presence of ALEx2 at one week of hospitalization in patients without ALEx2 on admission. Patients were followed until hospital discharge or death. Multivariable analysis was used to evaluate the association between ALEx2 on admission and during hospitalization and mortality. Results. Of the total of 298 patients, 60% were male, with a mean age of 60 years, and 74% of patients had at least one comorbidity. Of those, 137 (46%) patients were transferred to the intensive care unit and 66 (22.1%) patients died during hospitalization. ALEx2 on admission was present in 87 (29.2%) patients and was found to be independently associated with 1-week mortality (odds ratio (OR) = 3.55; 95% confidence interval (95%CI) 1.05–12.05). Moreover, 84 (39.8%) out of 211 patients without ALEx2 at admission developed de novo-ALEx2, which was independently associated with mortality during second week of hospitalization (OR = 6.09; 95%CI 1.28–29) and overall mortality (OR = 2.93, 95%CI 1.05–8.19). Conclusions. A moderate elevation of LFT during admission was associated with a poor short-term prognosis in patients hospitalized with COVID-19. In addition, moderate elevation of LFT at one week of hospitalization was an independent risk factor for overall mortality in these patients.